Microsatellite analysis of population structure in Slovak Pinzgau cattle - Šidlová, Veronika; Kasarda, Radovan; Moravčíková, Nina; Trakovická, Anna; Kadlečík, Ondrej (Acta Agraria Kaposváriensis, 2014)
The aim of the study was improve knowledge about population structure of Slovak Pinzgau cattle using genetic markers. Observed population structure was characterized by use of eight microsatellites. Each locus was tested for deviations from the Hardy-Weinberg Equilibrium (HWE). In general, breed was in genetic equilibrium, only locus BM1824 deviated from HWE. Cluster algorithms identify groups of related individuals without reference to prior information of the genetic subdivision. We considered 3 clusters that capture the major structure of the data (representative K value) and most likely reflect genealogical structuring. The chosen set of microsatellites confirmed the suitability for genetic structure assessment and its usefulness in determination of the subpopulations for Pinzgau cattle in Slovakia.